Sófocles, Traquinias 526 - Bañuls Oller, José Vicente (Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación. Centro de Estudios Helénicos, 2016)
In the first stasimon of Trachiniae, l. 526 there is an issue related to textual criticism which has not been solved yet. It is hard to understand the term Î¼Î¬Ï„Î·Ï noted in manuscripts, hence this fact leads to various assumptions. The most relevant was made by Zielinski, noting Î¸Î±Ï„Î®Ï . The interpretation given to Zielinski’s assumption causes several difficulties as it takes into account how the Chorus is depicted in the plot. This paper supports Zielinski’s assumption as it shows how it is related with a relevant source of information about the past events of women such as the iconography.